Apresiasi Ahmad Musțāfa Al-Marāġī Dalam Menafsirkan Q.S Al-Fātihah - Sohibi Harahap, Ali Musolli; Syafruddin, Syafruddin; Harahap, Amiruddin Tayib (Jurnal Ulunnuha, 2024)
Appreciation arises from the attitude of a commentator in evaluating an event/object of stud. It also appears as a way to get the deepest meaning in a work. Namely by studying and understanding in depth. Meanwhile, interpreting activities are also included in the appreciation section, because in interpreting you have to carry out an in-depth study first. This study aims to find out how a commentator, Ahmad Musțafa Al-Marāġī, appreciates letters in the Qur’an. This discussion focuses on Q.S Al-Fātihah in the book Tafsīr Al-Marāġī. Because, Ahmad Musțafa Al-Marāġī, in interpreting Q.S Al-Fātihah, first gives appreciation before studying the verses in more depth. Therefore, the author discusses this study with the title "Appreciation of Ahmad Musțafa Al-Marāġī in Interpreting Q.S Al-Fātihah". This study is library research, with the primary source being the book Tafsīr Al-Marāġī by Ahmad Musțafa Al-Marāġī. Meanwhile, the method used is descriptive analysis, and in processing and analyzing data using content analysis, the aim is to explore in depth the content (information) written in Tafsīr Al-Marāġī. As for the results of this discussion, it was found that; Ahmad Musțafa Al-Marāġī before interpreting the verses in Q.S Al-Fātihah: Firstly, gave two forms of appreciation to Q.S Al-Fātihah, namely; First, Aesthetic Appreciation in the form of Testimonials, namely; Understanding the Surah, Naming, and Content of Q.S Al-Fātihah, Signs of the verses of Q.S Al-Fātihah as the Main Content of the Qur'an; Problems of Monotheism, the Path to Happiness, Stories of Ancient People, People Who Go astray and Violate Allah's Limits, Arguments Supporting Testimonials. Secondly, Critical Appreciation of Testimonials to  the sentence basmalah (بسم الله الرحمن الرحيم).